Multi-Field Integrated Model With Profit-Spider Method In Mathematics Learning, Indonesian Language And Science Class Vi Sdn 39 Tanjung Saba - Maryetni Maryetni (Fakultas Sastra Universitas Ekasakti, 2017)
School education has an important role in improving the quality of human resources. School education is a process that involves educators, teaching materials, and learners.